Serological survey for equine viral arteritis in several municipalities in the Orinoquia region of Colombia/Monitoreo serologico de arteritis viral equina en municipios de la Orinoquia, Colombia - Gongora, Agustin O; Barrandeguy, Maria; Ciuoderis, Karl A (Revista MVZ (Medicina Veterinaria y Zootecnia), 2014)
Objective. The goal of this study was to determine the current status of the Equine Arteritis virus (EAV) in horse populations in the Orinoquia region of Colombia. Materials and methods. A transversal study was conducted by serological survey of equine (n=100) from 11 municipalities of the Colombian Orinoquia region. Serum samples were tested by virus seroneutralization assay according to the guidelines provided by the World Organization for Animal Health. Results. After testing was carried out no positives samples to EAV were found in the population analyzed. Conclusions. Although the sample size of the population screened in this study does not represent the total equine population size for the region or the country, data obtained has shown the absence of EAV infection in these animals. However, a wider study area including other regions of the country, with a feasible statistical design, would determine if this infection continues to be an exotic disease for Colombia. Key words: Antibodies, epidemiology, prevalence, virus (Source: DeCS). Objetivo. Determinar la condicion sanitaria relativa a la infeccion con el virus de la arteritis (VAE) en equinos de la Orinoquia, Colombia. Materiales y metodos. Se realizo un muestreo serologico transversal en equinos (n:100) provenientes de 11 municipios, de la region de la Orinoquia, Colombia. Los sueros fueron analizados por la tecnica de seroneutralizacion viral de acuerdo con lo recomendado por la Organizacion Internacional de Sanidad Animal (OIE). Resultados. No se identificaron reactores al VAE en la poblacion analizada. Conclusiones. Si bien la poblacion estudiada no representa el total de los equinos de la region, ni del pais, los datos obtenidos evidencian la ausencia de infeccion por VAE en estos animales. Un estudio ampliado, estadisticamente disenado, incluyendo otras regiones del pais permitiria determinar fehacientemente si esta infeccion continua siendo exotica para Colombia. Palabras clave: Anticuerpos, epidemiologia, prevalencia, virus (Fuente: DeCS).